Telaah Kritis Kebijakan Supervisi Pendidikan di Indonesia (UU No. 14 Tahun 2005 tentang Guru dan Dosen, PP No. 19 Tahun 2005 dan Penggantinya tentang Standar Nasional Pendidikan) - Nasrullah, Khoirudin (Lembaga Yasin AlSys, 2026)
Education is one of the fundamental pillars and an integral part of societal life, so every individual has an equal right to quality education. This study aimed to conduct a critical review of educational supervision policy in Indonesia by focusing the analysis on Law No. 14 of 2005 on Teachers and Lecturers and Government Regulation No. 19 of 2005 on National Education Standards, along with their subsequent replacement regulations. Educational supervision is positioned as a principal pillar of instructional quality assurance; however, its implementation often encounters regulatory ambiguities and a paradigm shift from administrative inspection to professional mentoring. This study employed a qualitative method with a library research approach and content analysis of various relevant regulations and scholarly literature. The findings indicate that although Law No. 14 of 2005 has affirmed teachers’ status as professionals, policy synchronization in Government Regulation No. 19 of 2005 (and its amendments up to Government Regulation No. 4 of 2022) still leaves overlapping roles between school supervisors and principals. The transformation of policy from the previous National Education Standards framework toward a new paradigm provides greater flexibility, but has not yet been fully accompanied by clear supervisory instruments that are adaptive to the demands of the digital era. This review concludes that strengthening educational supervision policy needs to be directed toward a collaborative clinical supervision model oriented to professional mentoring and meaningful learning, so that it does not merely stop at fulfilling administrative workload requirements.